Modern and late Pleistocene particulate organic carbon transport by the Amazon River: Insights from long-chain alkyl diols. (1st October 2019) - Häggi, Christoph; Schefuß, Enno; Sawakuchi, André O.; Chiessi, Cristiano M.; Mulitza, Stefan; Bertassoli, Dailson J.; Hefter, Jens; Zabel, Matthias; Baker, Paul A.; Schouten, Stefan
Abstract: The relative abundance of the C32 1, 15 long-chain alkyl diol (LCD) is an emerging proxy for the input of riverine aquatic particulate organic carbon (POC) into coastal oceans. This compound has the potential to complement other established proxies reflecting riverine terrestrial POC input and allows for a more nuanced assessment of riverine POC export to coastal seas. The current understanding of this proxy is, however, limited. In this study, we compare different indices for riverine sediment input to coastal marine waters (i.e. C32 1, 15-LCD, BIT index and Fe/Ca ratio) in a source-to-sink assessment in the Amazon River drainage system and the northeast South American continental margin, and we test their down-core applicability in a marine gravity core containing late Pleistocene fluvial Amazonian sediments. We show that the relative abundance of the C32 1, 15-LCD is highest in water bodies with low flow velocity and low turbidity such as the downstream portion of lowland tributaries and floodplain lakes. Relative C32 1, 15-LCD abundance is lowest in Andean white water tributaries where autotrophic productivity is hindered by high turbidity and high flow velocity. We also find that suspended particulate matter from all major tributaries during the extreme 2015 dry season has a similar LCD distribution to that of floodplain lakes. This indicates that the chemical composition of the tributaries is less relevant for the LCD distribution than their physical properties such as flow velocity and turbidity. Results from marine surface sediments offshore the Amazon River estuary show significant positive correlations between all three studied proxies. In contrast, we find that the relative C32 1, 15-LCD abundance in the down-core record is anti-correlated to the BIT index and Fe/Ca ratio. While BIT index and Fe/Ca ratio show high (low) values during Heinrich stadials (Dansgaard-Oeschger interstadials), the C32 1, 15-LCD proxy shows the opposite signal. BIT values are also higher during Marine Isotope Stage (MIS) 2 than during MIS 3, in contrast to trends in the C32 1, 15-LCD proxy. We posit that this pattern arises from a reduction in relative C32 1, 15-LCD abundance and total LCD productivity in the Amazon River during MIS 2 when less-humid conditions and lower sea level led to reduced area of floodplains. During Heinrich stadials, Andean sediment input increased and led to higher turbidity that resulted in lower C32 1, 15-LCD production. Our study shows that major changes in water discharge, sediment transport and river morphology can lead to discrepancies between the BIT index and the relative abundance of the C32 1, 15-LCD. Thus, we suggest that Amazonian aquatic and terrestrial POC pools had contrasting responses to changes related to both climate (e.g. increased Andean precipitation) and river morphology (e.g. steeper along-channel slope due to falling and low stand sea level).